The Meaning of Khalaqa and Its Derivation in Surah Ar-Rum (Semantic Analysis of Toshihiko Izutsu) - Mislannada Fiddaraini; FNU Yusroh; Rika Astari; Abdul Mukhlis (Indonesian Journal of Arabic Studies, 2022)
This study, entitled 'The Meaning of Khalaqa and its Derivation in Surah Ar-Rum (Semantic Study of Toshihiko Izutsu)' aims to describe the derivation of the word khalaqa in Surah Ar-Rum, explain its basic and relational meanings, explain the synchronic and diachronic words of khalaqa with a semantic perspective. Toshihiko Izutsu explains the world view of the derivation of the word khalaqa in Surah Ar-Rum. The method used in this research is descriptive with a qualitative approach. The type of research used is a literature study. The research design and framework are temporary because the research is open-ended, and this research is natural. The results of this study indicate that the form of the word khalaqa and its derivation in the surah Ar-Rum is found 10 times mentioned in 9 verses, some are in the form of file madi, fi'il mudari', and masdar. The basic meaning of each verse is creating, creation, and creation, and its relational meaning is related to the words Allah, Allah, Yabdaâ€™u, Yuâ€™iduhu, Fitrah, Yatafakkaru, as-Samawati wal-â€˜Ard, Alsinatikum wa Alwanikum, Azwaja, Turab, Basyar, Razaqakum, Yumitukum, yuhyikum, Daâ€™fin quwwatan, Ma yasyaâ€™u and Wa min Ayatihi. The synchronic meaning is explained through the method of interpretation which comes from the explanations of the interpretations of Ibn Katsir, Al-Maragi, and Tafsir Al-Misbah. The diachronic meaning of the word khalaqa and its derivation consists of three phases, namely pre-Qur'an, Qur'anic phase, and post-Qur'an. The resulting worldview can form the belief in the existence of Allah SWT with three types of components, namely a vertical relationship to Allah (hablun min Allah), a relationship to fellow humans (hablun minan-nas), and a close relationship to Allah through oneself (hablun binafsihi).ØªÙ‡Ø¯Ù Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ù…Ø¹Ù†ÙˆÙ†Ø© "Ù…Ø¹Ù†Ù‰ Ø®Ù„Ù‚ ÙˆØ§Ø´ØªÙ‚Ø§Ù‚Ù‡Ø§ ÙÙŠ Ø³ÙˆØ±Ø© Ø§Ù„Ø±ÙˆÙ… (Ø¯Ø±Ø§Ø³Ø© Ø¯Ù„Ø§Ù„ÙŠØ© Ø¹Ù†Ø¯ ØªÙˆØ´ÙŠÙ‡ÙŠÙƒÙˆ Ø¥ÙŠØ²ÙˆØªØ³Ùˆ)" Ø¥Ù„Ù‰ ÙˆØµÙ Ø§Ø´ØªÙ‚Ø§Ù‚ ÙƒÙ„Ù…Ø© Ø®Ù„Ù‚ ÙÙŠ Ø³ÙˆØ±Ø© Ø§Ù„Ø±ÙˆÙ…ØŒ ÙˆØ´Ø±Ø Ù…Ø¹Ø§Ù†ÙŠÙ‡Ø§ Ø§Ù„Ø£Ø³Ø§Ø³ÙŠØ© ÙˆØ§Ù„Ø¹Ù„Ø§Ø¦Ù‚ÙŠØ©ØŒ ÙˆØ´Ø±Ø Ø§Ù„Ù…ØªØ²Ø§Ù…Ù† ÙˆØ§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…ØªØ²Ø§Ù…Ù†Ø© Ù„Ù„Ø®Ù„Ù‚ Ù…Ù† Ù…Ù†Ø¸ÙˆØ± Ø¯Ù„Ø§Ù„ÙŠ: ØªÙˆØ´ÙŠÙ‡ÙŠÙƒÙˆ Ø¥ÙŠØ²ÙˆØªØ³ÙˆØŒ ÙˆÙŠØ´Ø±Ø Ø§Ù„Ù†Ø¸Ø±Ø© Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠØ© Ù„Ø§Ø´ØªÙ‚Ø§Ù‚ ÙƒÙ„Ù…Ø© Ø®Ù„Ù‚ ÙÙŠ Ø³ÙˆØ±Ø© Ø§Ù„Ø±ÙˆÙ….Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« ÙˆØµÙÙŠØ© Ø°Ø§Øª Ù…Ù†Ù‡Ø¬ Ù†ÙˆØ¹ÙŠ. Ù†ÙˆØ¹ Ø§Ù„Ø¨ØØ« Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù… Ù‡Ùˆ Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ø£Ø¯Ø¨. ØªØµÙ…ÙŠÙ… Ø§Ù„Ø¨ØØ« ÙˆØ¥Ø·Ø§Ø±Ù‡ Ù…Ø¤Ù‚ØªØ§Ù† Ù„Ø£Ù† Ø§Ù„Ø¨ØØ« Ù…ÙØªÙˆØØŒ ÙˆÙ‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø·Ø¨ÙŠØ¹ÙŠ.ØªØ´ÙŠØ± Ù†ØªØ§Ø¦Ø¬ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ Ø£Ù† Ø´ÙƒÙ„ ÙƒÙ„Ù…Ø© Ø®Ù„Ù‚ ÙˆØ§Ø´ØªÙ‚Ø§Ù‚Ù‡Ø§ ÙÙŠ Ø³ÙˆØ±Ø© Ø§Ù„Ø±ÙˆÙ… ÙˆØ¬Ø¯ 10 Ù…Ø±Ø§Øª Ø§Ù„Ù…Ø°ÙƒÙˆØ±Ø© ÙÙŠ 9 Ø¢ÙŠØ§Øª Ø¨Ø¹Ø¶Ù‡Ø§ Ø¹Ù„Ù‰ Ø´ÙƒÙ„ Ø§Ù„ÙØ¹Ù„ Ø§Ù„Ù…Ø§Ø¶ÙŠØŒ Ùˆ Ø§Ù„Ù…Ø¶Ø§Ø±Ø¹ØŒ Ùˆ Ø§Ù„Ù…ØµØ¯Ø±. Ø§Ù„Ù…Ø¹Ù†Ù‰ Ø§Ù„Ø£Ø³Ø§Ø³ÙŠ Ù„ÙƒÙ„ Ø¢ÙŠØ© Ù‡Ùˆ Ø§Ù„Ø®Ù„Ù‚ØŒ ÙˆØ§Ù„Ø®Ø§Ù„Ù‚ØŒ Ùˆ Ø§Ù„Ù…Ø®Ù„ÙˆÙ‚ØŒ ÙˆÙ…Ø¹Ù†Ø§Ù‡ Ø§Ù„Ø¹Ù„Ø§Ø¦Ù‚ÙŠ Ù…Ø±ØªØ¨Ø· Ø¨ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù„Ù‡ØŒ ÙˆØ§Ù„ÙØ·Ø±Ø©ØŒ Ùˆ Ù…Ù† Ø¢ÙŠØ§ØªÙ‡ ÙˆØ§Ù„Ø³Ù…Ø§ÙˆØ§Øª ÙˆØ§Ù„Ø£Ø±Ø¶ØŒ ÙˆØ§Ù„Ø£Ø²ÙˆØ§Ø¬ØŒ ÙˆØ§Ù„Ø¨Ø´Ø± Ùˆ Ø§Ù„ØªØ±Ø§Ø¨ Ùˆ ÙŠØ¨Ø¯Ø£ Ùˆ ÙŠØ¹ÙŠØ¯ Ùˆ Ø±Ø²Ù‚ Ùˆ ÙŠÙ…ÙŠØª Ùˆ ÙŠØÙŠÙŠ Ùˆ ÙŠØªÙÙƒØ±Ùˆ Ù…Ø§ ÙŠØ´Ø§Ø¡. ÙˆÙŠÙØ³Ø± Ù…Ø¹Ù†Ù‰ Ø§Ù„ØªØ²Ø§Ù…Ù† Ù…Ù† Ø®Ù„Ø§Ù„ Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªÙØ³ÙŠØ± Ø§Ù„Ø°ÙŠ ÙŠØ£ØªÙŠ Ù…Ù† ØªÙØ³ÙŠØ± Ø§Ø¨Ù† ÙƒØ«ÙŠØ± ÙˆØ§Ù„Ù…Ø±Ø§ØºÙŠ ÙˆØªÙØ³ÙŠØ± Ø§Ù„Ù…ØµØ¨Ø§Ø. ÙŠØªÙƒÙˆÙ† Ø§Ù„Ù…Ø¹Ù†Ù‰ Ø§Ù„ØªØ§Ø±ÙŠØ®ÙŠ Ù„ÙƒÙ„Ù…Ø© Ø§Ù„Ø®Ù„Ù‚ ÙˆØ§Ø´ØªÙ‚Ø§Ù‚Ù‡Ø§ Ù…Ù† Ø«Ù„Ø§Ø« Ù…Ø±Ø§ØÙ„ØŒ ÙˆÙ‡ÙŠ Ù…Ø±ØÙ„Ø© Ù…Ø§ Ù‚Ø¨Ù„ Ø§Ù„Ù‚Ø±Ø¢Ù† ÙˆØ§Ù„Ù…Ø±ØÙ„Ø© Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠØ© ÙˆÙ…Ø§ Ø¨Ø¹Ø¯ Ø§Ù„Ù‚Ø±Ø¢Ù†. ÙŠÙ…ÙƒÙ† Ù„ÙˆØ¬Ù‡Ø© Ø§Ù„Ù†Ø¸Ø± Ø§Ù„Ù†Ø§ØªØ¬Ø© Ø¥Ù„Ù‰ Ø§Ù„Ø¹Ø§Ù„Ù… Ø£Ù† ØªÙƒÙˆÙÙ‘Ù† Ø§Ù„Ø¥ÙŠÙ…Ø§Ù† Ø¨ÙˆØ¬ÙˆØ¯ Ø§Ù„Ù„Ù‡ Ø³Ø¨ØØ§Ù†Ù‡ ÙˆØªØ¹Ø§Ù„Ù‰ Ø¨Ø«Ù„Ø§Ø«Ø© Ø£Ù†ÙˆØ§Ø¹ Ù…Ù† Ø§Ù„Ù…ÙƒÙˆÙ†Ø§ØªØŒ ÙˆÙ‡ÙŠ Ø§Ù„Ø¹Ù„Ø§Ù‚Ø© Ø§Ù„Ø±Ø£Ø³ÙŠØ© Ø¨Ø§Ù„Ù„Ù‡ (ØØ¨Ù„ Ù…Ù† Ø§Ù„Ù„Ù‡)ØŒ ÙˆØ§Ù„Ø¹Ù„Ø§Ù‚Ø© Ù…Ø¹ Ø¥Ø®ÙˆØ§Ù†Ù†Ø§ Ù…Ù† Ø§Ù„Ø¨Ø´Ø± (ØØ¨Ù„ Ù…Ù† Ø§Ù„Ù†Ø§Ø³)ØŒ ÙˆØ§Ù„Ø¹Ù„Ø§Ù‚Ø© Ø§Ù„ÙˆØ«ÙŠÙ‚Ø© Ø¨Ø§Ù„Ù„Ù‡ Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„Ø°Ø§Øª. (ØØ¨Ù„ Ø¨Ù†ÙØ³Ù‡).